2015
DOI: 10.4049/jimmunol.1402088
|View full text |Cite
|
Sign up to set email alerts
|

MiR-127 Modulates Macrophage Polarization and Promotes Lung Inflammation and Injury by Activating the JNK Pathway

Abstract: A polarized macrophage response is presumed to have a pivotal role in a variety of immunological pathophysiology. However, the molecular mechanism underlying macrophage functional shaping remains largely unknown. In this study, we reveal a pivotal role of miR-127 in macrophage development and thereby the pathogenesis of inflammation and lung injury. In particular, miR-127 was demonstrated to be prominently induced upon TLR engagement and repressed by the M2-prone cytokines. Enforced expression of miR-127 in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 56 publications
6
122
1
1
Order By: Relevance
“…The present study indicated that miR-127 was prominently induced in the inflammation-related pulmonary disorders such as LPS, bleomycin, or immunocomplex-induced lung injury and inflammation [22,23], which suggesting a potential role of miR-127 in the inflammatory signaling and lung pathology. Our results showed that the expression of miR-127 in lung tissue BALF were decreased gradually with the increase of dose and the passage of time in the LPS groups.…”
Section: The Expression Of Microrna-155 and 127 In The Neonatal Sd Rasupporting
confidence: 52%
“…The present study indicated that miR-127 was prominently induced in the inflammation-related pulmonary disorders such as LPS, bleomycin, or immunocomplex-induced lung injury and inflammation [22,23], which suggesting a potential role of miR-127 in the inflammatory signaling and lung pathology. Our results showed that the expression of miR-127 in lung tissue BALF were decreased gradually with the increase of dose and the passage of time in the LPS groups.…”
Section: The Expression Of Microrna-155 and 127 In The Neonatal Sd Rasupporting
confidence: 52%
“…M1 macrophages are associated with high levels of proinflammatory cytokines and have detrimental effects and toxicity [41]; whereas, M2 macrophages produce anti-inflammatory mediators and exhibit regeneration and protection [40]. The reduction of M1 macrophages alleviates damaging inflammatory activity in the lung [41].…”
Section: Discussionmentioning
confidence: 99%
“…Although individual expression of CTGF in lung tissue induced only mild fibrosis, 33 inhibiting the expression of CTGF can prevent fibrosis formation. 34 microRNA has a lot of different target genes. In the same way, the same target genes often jointly regulated by many different miRNAs.…”
Section: Target Genes and Proteins Expression In Test And Control Groupsmentioning
confidence: 99%